2009
DOI: 10.3163/1536-5050.97.3.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PubMed filters used for evidence-based searching: validation using relative recall

Abstract: Sensitive and Specific Clinical Queries filters used to answer questions about therapy will result in a list of clinical trials but cannot be expected to identify only methodologically sound trials. The Specific Clinical Queries filters are not suitable for questions regarding therapy that cannot be answered with randomized controlled trials. Combining AIM with specific PubMed filters yields the highest precision in the Cochrane dataset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…When applied to the whole Medline database, the Clinical Queries broad filter retained 99% of hand-selected studies, while the narrow filter retained 93% [27]. Hoogendam et al found similar results [31]. Our study confirmed the high sensitivity of the Clinical Queries filters when applied to specific clinical questions.…”
Section: Discussionsupporting
confidence: 82%
“…When applied to the whole Medline database, the Clinical Queries broad filter retained 99% of hand-selected studies, while the narrow filter retained 93% [27]. Hoogendam et al found similar results [31]. Our study confirmed the high sensitivity of the Clinical Queries filters when applied to specific clinical questions.…”
Section: Discussionsupporting
confidence: 82%
“…The search focused on RCTs published between 1 January 2013 and 31 December 2017, using PubMed's Clinical Trial[ptyp] filter. Use of this filter was intended to maximize sensitivity to ensure that no relevant RCTs were excluded . Journals listed in the addiction category of Google Scholar metrics were selected based on their h5‐index.…”
Section: Methodsmentioning
confidence: 99%
“…We used those terms to identify published phase 2 trials for each drug using the PubMed search engine with the “clinical trial” filter 6 (January 1, 2005, to April 30, 2014). One reviewer (D.D.G.B.)…”
Section: Methodsmentioning
confidence: 99%